Identification of target proteins of clinical immunity to Plasmodium falciparum in a region of low malaria transmission. Issue 2 (April 2018) - Sakamoto, Hirokazu; Takeo, Satoru; Takashima, Eizo; Miura, Kazutoyo; Kanoi, Bernard N.; Kaneko, Takamasa; Han, Eun-Taek; Tachibana, Mayumi; Matsuoka, Kazuhiro; Sattabongkot, Jetsumon; Udomsangpetch, Rachanee; Ishino, Tomoko; et al.
Abstract: The target molecules of antibodies against falciparum malaria remain largely unknown. Recently we have identified multiple proteins as targets of immunity against Plasmodium falciparum using African serum samples. To investigate whether potential targets of clinical immunity differ with transmission intensity, we assessed immune responses in residents of low malaria transmission region in Thailand. Malaria asymptomatic volunteers (Asy: n = 19) and symptomatic patients (Sym: n = 21) were enrolled into the study. Serum immunoreactivity to 186 wheat germ cell-free system (WGCFS)-synthesized recombinant P. falciparum asexual-blood stage proteins were determined by AlphaScreen, and subsequently compared between the study groups. Forty proteins were determined as immunoreactive with antibody responses to 35 proteins being higher in Asy group than in Sym group. Among the 35 proteins, antibodies to MSP3, MSPDBL1, RH2b, and MSP7 were significantly higher in Asy than Sym (unadjusted p < 0.005) suggesting these antigens may have a protective role in clinical malaria. MSP3 reactivity remained significantly different between Asy and Sym groups even after multiple comparison adjustments (adjusted p = 0.033). Interestingly, while our two preceding studies using African sera were conducted differently (e.g., cross-sectional vs. longitudinal design, observed clinical manifestation vs. functional activity), those studies similarly identified MSP3 and MSPDBL1 as potential targets of protective immunity. This study further provides a strong rationale for the application of WGCFS-based immunoprofiling to malaria vaccine candidate and biomarker discovery even in low or reduced malaria transmission settings. Highlights: WGCFS generated P. falciparum recombinant proteins are immunoreactive to human sera from low endemic Thailand. Four P. falciparum antigens are plausible targets of clinical immunity. WGCFS and AlphaScreen system are invaluable tools for malaria vaccine candidate and biomarker discovery.